THE ROLE OF ENVIRONMENT AND NUTRITION ON THE PREVALENCE OF STUNTING IN PAHLAWAN VILLAGE BATUBARA REGENCY - Harahap, Dama Kania; Ma'arif, Muhammad Ghozali; Nadia, Rafa; Tama, Ray Ade; Hasibuan, Dini Nurbaiti; Syam, Abdi Mubarak (PERSPEKTIF: Journal of Social and Library Science, 2024)
Stunting remains a significant health issue in Desa Pahlawan, Kecamatan Tanjung Tiram, driven by environmental, sanitation, and nutritional factors. This study explores the relationship between these factors and the prevalence of stunting, while examining the potential of local resources, such as marine fish, for improving nutrition. A qualitative approach, using in-depth interviews and field observations, revealed that poor access to clean water, low sanitation quality, and limited use of local food resources significantly contribute to stunting. Additionally, inadequate dietary practices and a lack of awareness about balanced nutrition exacerbate the issue. Though intervention programs such as community education and collaboration with local health posts have been implemented, further coordinated efforts are necessary for long-term change. This research provides insights into the causes of stunting in Desa Pahlawan and offers locally-based recommendations for more effective interventions.